2013
DOI: 10.1136/bcr-2013-200870
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral calf hypertrophy and focal myositis induced by S1 radiculopathy: dramatic response to steroid treatment

Abstract: SUMMARYUnilateral enlargement of the calf in a 57-year-old man with S1 radiculopathy is described in this case report. Short tau inversion recovery-weighted imaging provided evidence of selective hypertrophy and a high signal intensity of the gastrocnemius and soleus. Histopathological analysis of the gastrocnemius revealed an endomysial inflammatory infiltrate and marked denervation lesions. Marked signs of denervation are suggestive of focal myositis secondary to neurogenic damage. The patient was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Another theory is the mechanical process in terms of repeated microtrauma due to walking on denervated muscle, which could be the cause of myositis. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Another theory is the mechanical process in terms of repeated microtrauma due to walking on denervated muscle, which could be the cause of myositis. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Treatment can either be surgical or conservative. Oral corticosteroids with prednisone or prednisolone at a dose of 15-45 mg per day has been reported for its effectiveness in cases of unilateral calf hypertrophy induced by radiculopathy with combined focal myositis [3]. Early detection is critical in deciding the proper treatment option and necessary for preventing deleterious effects of progressive muscle pseudohypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment can involve surgery or can be nonsurgical. In nonsurgical treatment, an injection of botulinum toxin [ 13 ] and steroid medication [ 14 ] are effective. In surgical treatment, Gibson and Waddell [ 15 ] reported that microdiscectomy is the effective way to reduce radiculopathy and muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%